An inelastic-state based procedure to calculate the force demands along building height for recentering steel building frames. (15th February 2023) - Li, Junlin; Wang, Wei
Highlights: A practical procedure to calculate force demands along building height for recentering building frames is proposed. The proposed procedure includes higher mode effect based on inelastic-state of the considered system. The building frame designed with the proposed procedure may develop a uniform deformation pattern along building height. The procedure is applicable to considered systems with different story numbers. Abstract: To eliminate the residual deformation of conventional seismic-resistant steel building frames, numerous resilient building frames with recentering capacities were developed. However, prior researches indicated the severe higher mode effect of such structural systems may lead to nonuniform deformation pattern. To improve the seismic performance of recentering building frames, this paper develops a practice-oriented procedure to calculate the force demands along building height. The procedure includes the effect of hysteretic principle based on the expected structural inelastic-state. To validate the proposed procedure, multiple designs were performed on 27 demonstration building frames. Nonlinear response history analyses were conducted to evaluate the applicability of the proposed procedure. Based on the results of numerical analyses conducted in this research, it was found that the considered system designed in line with the prevailing design procedure may lead to unsatisfactory deformation in top or bottom stories. Using the force demands from the proposed procedure will help the considered structural system develop a more uniform deformation pattern along building height.